Evaluation of hepatitis C treatment-as-prevention within Australian prisons (SToP-C): a prospective cohort study. (July 2021) - Hajarizadeh, Behzad; Grebely, Jason; Byrne, Marianne; Marks, Pip; Amin, Janaki; McManus, Hamish; Butler, Tony; Cunningham, Evan B; Vickerman, Peter; Martin, Natasha K; McHutchison, John G; Brainard, Diana M; et al.
Summary: Background: Limited empirical evidence exists for the effectiveness of hepatitis C virus (HCV) treatment-as-prevention. The Surveillance and Treatment of Prisoners with hepatitis C (SToP-C) study aimed to assess the effect of HCV treatment-as-prevention in the prison setting. Methods: SToP-C was a prospective study, including a before-and-after analysis, within a cohort of people incarcerated in two maximum-security prisons (male) and two medium-security prisons (one male, one female) in New South Wales, Australia. All prison inmates aged at least 18 years were eligible for enrolment. After HCV testing, participants were monitored for risk behaviours and HCV infection, among three sub-populations: uninfected (HCV antibody-negative); previously infected (HCV antibody-positive, HCV RNA-negative); and infected (HCV antibody and HCV RNA-positive). Uninfected participants were followed up every 3–6 months to detect HCV primary infection and previously infected participants were followed up every 3–6 months to detect re-infection. Participants with HCV infection were assessed for treatment, initially standard-of-care treatment (administered by prison health services) from 2014 to mid-2017, then direct-acting antiviral (DAA) treatment scale-up from mid-2017 onwards (12 weeks of sofosbuvir plus velpatasvir, administered through SToP-C). Participants were followed up until study closure in November, 2019. The primary study outcome was HCV incidence before and after DAA treatment scale-up among participants at risk of HCV primary infection or re-infection. This study is registered with ClinicalTrials.gov, NCT02064049 . Findings: Between Oct 30, 2014, and Sept 30, 2019, 3691 participants were enrolled in the SToP-C study. 719 (19%) participants had detectable HCV RNA, 2240 (61%) were at risk of primary HCV infection, and 725 (20%) were at risk of re-infection at baseline. DAA treatment was initiated in 349 (70%) of 499 eligible participants during the treatment scale-up period. The HCV incidence analysis comprised 1643 participants at risk of HCV infection or re-infection during longitudinal follow-up (median age 33 years [IQR 27–42]; 1350 [82%] male). 487 (30%) of 1643 participants reported injecting drugs in prison. HCV incidence decreased from 8·31 per 100 person-years in the pre-treatment scale-up period to 4·35 per 100 person-years in the post-treatment scale-up period (incidence rate ratio [IRR] 0·52 [95% CI 0·36–0·78]; p=0·0007). The incidence of primary infection decreased from 6·64 per 100 person-years in the pre-treatment scale-up period to 2·85 per 100 person-years in the post-treatment scale-up period (IRR 0·43 [95% CI 0·25–0·74]; p=0·0019), whereas the incidence of re-infection decreased from 12·36 per 100 person-years to 7·27 per 100 person-years (0·59 [0·35–1·00]; p=0·050). Among participants reporting injecting drugs during their current imprisonment, the incidence of primary infection decreased from 39·08 per 100 person-years in the pre-treatment scale-up period to 14·03 per 100 person-years in the post-treatment scale-up period (IRR 0·36 [95% CI 0·16–0·80]; p=0·0091), and the incidence of re-infection decreased from 15·26 per 100 person-years to 9·34 per 100 person-years (0·61 [0·34–1·09]; p=0·093). The adjusted analysis (adjusted for age, Indigenous Australian ethnicity, duration of stay in prison, previous imprisonment, injecting drug use status, and prison site) indicated a significant reduction in the risk of HCV infection between the pre-DAA treatment scale-up and post-DAA treatment scale-up periods (adjusted hazard ratio 0·50 [95% CI 0·33–0·76]; p=0·0014). Interpretation: DAA treatment scale-up was associated with reduced HCV incidence in prison, indicative of a beneficial effect of HCV treatment-as-prevention in this setting. These findings support broad DAA treatment scale-up within incarcerated populations. Funding: Australian National Health and Medical Research Council Partnership Project Grant and Gilead Sciences.